The immatures of three neotropical species of palpomyia meigen (Diptera, culicomorpha, ceratopogonidae) - Anjos Dos Santos, Danielle (2020)
The first description of the fourth instar larva and pupa of Palpomyia mapuche Spinelli, Grogan & Ronderos and the pupa of P. subfuscula Ingram & Macfie are provided, as well as the redescription of the pupa of P. subaspera (Coquillett). Studied specimens were collected in lotic environments of Argentinian Patagonia, in Neuquén and Chubut Provinces. The described stages were examined and illustrated with a phase-contrast microscope. The larva was examined using a scanning electron microscope. Data on the bionomics for P. mapuche and new records for the three species are provided.